Novel nanoscale hybrid materials - Chauhan, Bhanu P. S. (Hoboken, NJ, USA : John Wiley & Sons, 2018)
A comprehensive and interdisciplinary resource filled with strategic insights, tools, and techniques for the design and construction of hybrid materials. Hybrid materials represent the best of material properties being combined for the development for materials with properties otherwise unavailable for application requirements. Novel Nanoscale Hybrid Materials is a comprehensive resource that contains contributions from a wide range of noted scientists from various fields, working on the hybridization of nanomolecules in order to generate new materials with superior properties. The book focuses on the new directions and developments in design and application of new materials, incorporating organicnorganic polymers, biopolymers, and nanoarchitecture approaches. This book delves deeply into the complexities that arise when characteristics of a molecule change on the nanoscale, overriding the properties of the individual nanomolecules and generating new properties and capabilities altogether. The main topics cover hybrids of carbon nanotubes and metal nanoparticles, semiconductor polymer/biopolymer hybrids, metal biopolymer hybrids, bioorganicnorganic hybrids, and much more. This important resource: -Addresses a cutting-edge field within nanomaterials by presenting groundbreaking topics that address hybrid nanostructures -Includes contributions from an interdisciplinary group of chemists, physicists, materials scientists, chemical and biomedical engineers -Contains applications in a wide-range of fields-including biomedicine, energy, catalysis, green chemistry, graphene chemistry, and environmental science -Offers expert commentaries that explore potential future avenues of future research trends Novel Nanoscale Hybrid Materials is an important resource for chemists, physicists, materials, chemical and biomedical engineers that offers the most recent developments and techniques in hybrid nanostructures.
Silanols as building blocks for nanomaterials -- Biomacromolecule enabled synthesis of inorganic materials -- Multilayer assemblies of biopolymers : synthesis, properties, and applications -- Functionalization of p3ht-based hybrid materials for photovoltaic applications -- Insights on nano-filler reinforced polysiloxane hybrids -- Nanophotonics with hybrid nanostructures : new phenomena and new possibilities -- Drug delivery vehicles from stimuli-responsive block copolymers -- Mechanical properties of rubber toughened epoxy nanocomposites -- Metal complexes in reverse micelles -- Heterogenized catalysis on metals impregnated mesoporous silica.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 12, 2018).
Keywords: Nanostructured materials; Composite materials; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Composite materials; Nanostructured materials; Electronic books